Long-Term Effects of Gonadotropin-Releasing Hormone Agonists and Add-Back in Adolescent Endometriosis - Gallagher, Jenny Sadler (J Pediatr Adolesc Gynecol, 2018)
STUDY OBJECTIVE: To explore the potential occurrence of long-term side effects and tolerability of gonadotropin-releasing hormone agonist (GnRHa) plus 2 different add-back regimens in adolescent patients with endometriosis DESIGN: Follow-up questionnaire sent in 2016 to patients who participated in a drug trial between 2008–2012 SETTING: Tertiary care center in Boston, MA. PARTICIPANTS: Females with surgically confirmed endometriosis (n=51) who enrolled in a GnRHa plus add-back trial as adolescents INTERVENTIONS: Leuprolide depot 11.25 mg intramuscular injection every 3 month, plus oral norethindrone acetate 5 mg daily or oral norethindrone acetate 5 mg daily plus oral conjugated equine estrogens 0.625 mg daily. MAIN OUTCOME MEASURE(S): Side effects during and after treatment, irreversible side effects, changes in pain, overall satisfaction RESULTS: The response rate was 61%. Almost all (96%) reported side effects during treatment; 80% reported side effects lasting > 6 months after stopping treatment. Almost half (45%) reported side effects they considered irreversible, including memory loss, insomnia, and hot flashes. Despite side effects, subjects rated GnRHa plus add-back as the most effective hormonal medication for treating endometriosis pain; two thirds (16/25) would recommend it to others. More subjects who received a modified two drug add-back regimen versus standard one drug add-back would recommend GnRHa and felt it was the most effective hormonal medication. CONCLUSION: Subjects felt GnRHa plus add-back was effective and would recommend it to others, despite significant side effects. Those who received two drug add-back reported more success than those who received standard add-back. A subset of patients reported irreversible side effects. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT00474851